2018
DOI: 10.1021/acs.iecr.8b02625
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Combustion of Toluene over Cobalt Oxides Supported on Graphitic Carbon Nitride (CoOx/g-C3N4) Catalyst

Abstract: Graphitic carbon nitride (g-C3N4) supported CoOx catalysts were prepared by the impregnation method and comprehensively characterized by XRD, N2 physisorption, TEM, H2-TPR, and XPS. The catalytic performance tested by catalytic combustion of toluene indicates that 10% CoOx/g-C3N4 catalyst exhibits the highest activity, achieving a toluene conversion of 90% at a temperature of approximately 279 °C, compared with other CoOx catalysts supported on SBA-15, γ-Al2O3 and activated carbon (AC). The specific structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…It is worth noting that 13V 2 O 5 /g-C 3 N 4 has the highest surface O ads /O latt ratio among these catalysts. Previous studies have shown that the surface-adsorbed oxygen (O ads ), which is located at surface defects, is easier to reduce. Other literature has also shown that the surface-adsorbed oxygen is the most active species in aerobic oxidation, which promotes the exchange of gaseous oxygen with the surface-adsorbed ones. Since a high surface O ads /O lat ratio means the facile activation of oxygen molecules on the catalyst, the above results are quite consistent with the catalytic activities.…”
Section: Results and Discussionsupporting
confidence: 69%
“…It is worth noting that 13V 2 O 5 /g-C 3 N 4 has the highest surface O ads /O latt ratio among these catalysts. Previous studies have shown that the surface-adsorbed oxygen (O ads ), which is located at surface defects, is easier to reduce. Other literature has also shown that the surface-adsorbed oxygen is the most active species in aerobic oxidation, which promotes the exchange of gaseous oxygen with the surface-adsorbed ones. Since a high surface O ads /O lat ratio means the facile activation of oxygen molecules on the catalyst, the above results are quite consistent with the catalytic activities.…”
Section: Results and Discussionsupporting
confidence: 69%
“…But further increase in the cobalt loading did not enhance the catalytic efficiency, so that Co15/Sep exhibited similar catalytic activity for toluene degradation with that of Co20/ Sep. This finding is in agreement with Luo et al 40 study which reported that increasing the cobalt loading from 5 to 10% will enhance the catalytic efficiency of the catalyst with no enhancement in higher than 10% cobalt loadings. Table 2 makes a comparison on the catalytic activity of Co20/Sep in T 50 and T 90 with cobalt catalysts on different supports for removal of toluene reported by other researchers.…”
Section: Catalytic Activitysupporting
confidence: 89%
“…[53] T A B L E 2 Summary of the reported data of toluene combustion over Co-based catalysts and cobalt oxide catalysts [42] Co/Sr CeO 2 Toluene 1,000 20,000 h −1 . 237 253 Luo et al [43] L-12 Toluene 1,000 10,000 h −1 263 272 Feng et al [44] Co 3 O 4 NC Toluene 1,000 20,000 h −1 264 267 Zhang et al [10] Co 3 O 4 Toluene 1,000 40,000 ml g −1 h −1 262 268 Mo et al [45] Spherical Co 3 O 4 Toluene 1,000 20,000 ml g −1 h −1 249 266 Wang et al [46] Co 1.5 Mn 1.5 O 4 Toluene 1,000 30,000 ml g −1 h −1 263 267 Jiang et al [25] 3D Co 3 O 4 C Toluene 1,000 48,000 ml g −1 h −1 240 248 Ren et al [9] La 0.95 Ag 0.05 CoO 3 Toluene 1,000 30,000 cm 3 g −1 h −1 238 268 Liu et al [47] CuCo 0.5 /C Toluene 1,000 40,000 ml g −1 h −1 237 243 Chen et al [48] Ce…”
Section: Catalyst Performancementioning
confidence: 99%
“…In the midst of all the catalysts, the Ce 0.07 CoO shows the best catalytic activity when the temperature is lower than 220 C; however, Ce 0.05 CoO exhibits superior catalytic oxidation performance while temperature higher than 220 C and achieves the toluene conversion of 90% at 238 C that is 19 C lower than that of the Co 3 O 4 C. For the past few years, extensive researches have been carried out on the catalytic oxidation of toluene over Co-based catalysts, the catalytic activities (evaluated by T 50% and T 90% ) of some of them are listed in Table 2. A lot of data shows, the Ce 0.05 CoO sample exhibits a better catalytic activity than many of them, such as CoO x /g-C 3 N 4 (T 50% = 268.2 C, T 90% = 279.2 C), [43] Co/Sr CeO 2 (T 50% = 237 C, T 90% = 253 C), [44] L-12 (T 50% = 263 C, T 90% = 272 C), [45] Co 3 O 4 NC (T 50% = 264 C, T 90% = 267 C), [10] Co 3 O 4 (T 50% = 262 C, T 90% = 268 C), [46] spherical Co 3 O 4 (T 50% = 249 C, T 90% = 266 C), [47] Co 1.5 Mn 1.5 O 4 (T 50% = 263 C, T 90% = 267 C), [25] 3D Co 3 O 4 C (T 50% = 240 C, T 90% = 248 C), [9] La 0.95 Ag 0.05 CoO 3 (T 50% = 238 C, T 90% = 268 C), [48] CuCo 0.5 /C (T 50% = 237 C, T 90% = 243 C). [52] Figure 9b discloses the yields of CO 2 over different catalysts.…”
Section: Catalyst Performancementioning
confidence: 99%